Social harms in female-initiated HIV prevention method research: state of the evidence - Montgomerya, Elizabeth T.; Robertsa, Sarah T.; Nelb, Annalene; Malherbeb, Mariette; Torjesenc, Kristine; Bunged, Katherine; Singhd, Devika; Baetene, Jared M.; Marrazzof, Jeanne; Chirenjeg, Z. Mike; Kabwigu, Samuel; Beigi, Richard; et al. (AIDS (London, England), 2019)
Assessment of safety is an integral part of real-time monitoring in clinical trials. In HIV prevention research, safety of investigational products and trial participation has been expanded to include monitoring for ‘social harms’, generally defined as negative consequences of trial participation that may manifest in social, psychological, or physical ways. Further research on social harms within HIV prevention research is needed to understand the potential safety risks for women and advance the implementation of prevention methods in real-world contexts. Secondary analysis of quantitative data from three randomized, double-blind, placebo-controlled trials of microbicide candidates in sub-Saharan Africa was conducted. Additionally, we assessed data from two prospective cohort studies that included participants who became HIV-positive or pregnant during parent trials.
Keywords: Africa; HIV; Microbicide; Social harms; Women